Fiscal Policy And Growth in Developing Asia - Arnelyn May Abdon; Gemma Esther Estrada; Minsoo Lee; Donghyun Park (Asian Development Bank (ADB), 2014)
In this paper we empirically explore the relationship between fiscal policy and economic growth in developing Asia. The region's overall level of taxes and government spending are substantially lower than those prevailing in advanced economies. Nevertheless, there are conceptual grounds why fiscal policy, including the composition of taxes and government spending, can have a significant effect on growth, as our empirical analysis shows. In line with economic theory, property taxes have a more benign impact on growth than direct taxes, and spending more on education has a sizable positive impact on growth.
hdl:11540/4209
Keywords: H20; H50; 330; fiscal policy; growth; taxation; government spending; Asia; Finanzpolitik; Besteuerungsverfahren; Öffentliche Ausgaben; Wirtschaftswachstum; Asien